KAJIAN EKSPLORASI PROFIL USAHA MIKRO KECIL DAN MENENGAH SERTA STRATEGI PENGEMBANGANNYA DI KOTA TERNATE - Rahmat Sabuhari; Ruslan A Kamis; Safri Panigoro; Zulaiha Husen (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2022)
The global crisis due to the COVID-19 pandemic in 2020 caused many MSME production activities to stop and people's purchasing power to decline, therefore the right strategy was needed to overcome these problems. The purpose of this study is to identify the profile of Micro, Small, and Medium Enterprises that are devoted to restaurant businesses and providers of souvenirs typical of North Maluku, identify various real problems faced by MSME business actors so as to make it easier for the Ternate City Government to provide solutions they are facing, and find out business strategies that have been carried out by MSME actors in Ternate City in solving the problems they face so that the strategic solutions that will be offered can be more effective and efficient. The analytical method used is to use reports from interviews, summaries, and conclusions. The results of the discussion found that MSMEs in the food sector have not been able to implement the right strategy to increase sales during the COVID-19 pandemic, which is not known when it will end. Finally, MSME actors are expected to be able to survive, grow, and develop by using appropriate business strategies.